Significance of Charlson co-morbidity index as predictive factor for post-op complications after radical nephrectomy - Mughal, Nazish; Mahar, Naveed Ahmed; Bin Shaheen, Usama; Qureshi, Harris Hassan; Akhtar, Naseem; Kalwar, Sara Rasheed; Hashmi, Altaf (Journal of the Pakistan Medical Association, 2024)
The current study planned to explore the correlation between an elevated Charlson Comorbidity Index score and post-operative complications following radical nephrectomy in patients with renal cell carcinoma. A total of 70 patients aged 30-80 years undergoing radical nephrectomy were categorised into low Charlson Comorbidity Index score <4 group A and high score >4 group B. Post-operatively, complications were noted in 21(30%) patients, with higher grades more prevalent in the group B patients (relative risk: 1.96, p=0.004). The finding underscored the importance of considering comorbidities in assessing the risk of complications following radical nephrectomy. Key Words: Charlson comorbidity index, Renal tumour, Renal cell carcinoma, Radical nephrectomy.